Kinematic and EMG Comparison Between Variations of Unilateral Squats Under Different Stabilities - van den Tillaar, Roland; Larsen, Stian (Sports Medicine International Open, 2020)
The purpose of the study was to compare kinematics and muscle activity between two variations of unilateral squats under different stability conditions. Twelve male volunteers (age: 23±5 years, mass: 80±17 kg, height: 1.81±0.11 m, strength-training experience: 4.3±1.9 years) performed four repetitions with the same external load (≈4RM). Two variations (with the non-stance leg forwards vs. backwards) were performed in a Smith-machine and free-weight condition. The variables were barbell velocity, lifting time and surface electromyography activity of the lower extremity and trunk muscles during the descending and ascending phase. The main findings were 1) peak force was higher when performing the unilateral squats in the Smith machine; 2) peak ascending barbell velocity increased from repetition 3–4 with free weight; and 3) muscle activity from the rectus femoris, vastus lateral, biceps femoris, gluteus medius, and erector spinae increased with repetitions, whereas gluteus, and medial vastus and shank muscles were affected by the conditions. It was concluded that more peak force could be produced because of increased stability. However, peak barbell velocity increased from repetition to repetition in free-weight unilateral squats, which was probably because the participants grew more comfortable. Furthermore, increased instability causes more gluteus and vastus medial activation and foot variations mainly affected the calf muscles.
Keywords: strength; electromyography; stability; force